2019
DOI: 10.1002/ajhb.23382
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of the healthiest body in a market‐integrating indigenous population in Argentina: Fat idealization and gendered generational differences

Abstract: ObjectivesMarket integration seems to induce gender‐specific generational change in health‐related perceptions of body size. We predicted that among the Qom of Argentina, younger women would perceive comparatively thinner bodies as healthiest, demonstrating thin‐idealizing body norms, and older women would retain culturally rooted perceptions of heavier bodies as healthiest. As traditional and globalized body size ideals are different for men, we predicted that men would perceive normal bodies as healthiest an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
2
1
Order By: Relevance
“…Gender and age are thought to be strong determinants of the internalization of body size norms and body image, with women and younger generations more often susceptible to media-driven internalization of the thin ideal and body dissatisfaction (Esnaola et al, 2010;Sepúlveda & Calado, 2012). While body size norms differed by gender and age in 2010, with older women perceiving categorically overweight bodies as healthiest (Daiy et al, 2019), in this group, we found no statistical differences between genders and ages. Despite this, the qualitative interviews suggested that body norms and body image were internalized differently based on gender.…”
Section: Gender and Age Differencescontrasting
confidence: 64%
See 2 more Smart Citations
“…Gender and age are thought to be strong determinants of the internalization of body size norms and body image, with women and younger generations more often susceptible to media-driven internalization of the thin ideal and body dissatisfaction (Esnaola et al, 2010;Sepúlveda & Calado, 2012). While body size norms differed by gender and age in 2010, with older women perceiving categorically overweight bodies as healthiest (Daiy et al, 2019), in this group, we found no statistical differences between genders and ages. Despite this, the qualitative interviews suggested that body norms and body image were internalized differently based on gender.…”
Section: Gender and Age Differencescontrasting
confidence: 64%
“…By 2010, these values increased to 76% and 63% (Lagranja et al, 2015). A 2010 cross‐sectional study investigating perceptions of body size suggested that older Qom women residing in NamQom perceive overweight bodies as healthy, while younger women perceive thinner bodies as healthy; the study also found that men prefer clinically “normal”‐BMI body sizes (Daiy et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation